2017
DOI: 10.1242/jeb.142430
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive skills and the evolution of social systems

Abstract: How do animal social skills influence evolution? Complex animal social behaviors require many cognitive skills including individual recognition and observational learning. For social systems to evolve, these abilities need to be transmitted genetically or culturally and supported by the evolution of underlying neural systems. Because animal skill sets are so varied, it seems best to describe animal cognitive behaviors as being a social calculus that can change with experience, which has evolved to match and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 95 publications
(116 reference statements)
0
29
0
Order By: Relevance
“…For instance, testosterone shifts player strategy to enhance social status in an experimental gambling paradigm (Dreher et al, 2016). Hence, AR antagonism may have led to deficits in the recognition of social opportunity (Berghe, 2014;Fernald, 2017). Multiple sensory modalities are likely involved in an ND male's ability to recognize and act on social opportunity .…”
Section: Androgen Signaling Governs Multiple Aspects Of the Social Camentioning
confidence: 99%
“…For instance, testosterone shifts player strategy to enhance social status in an experimental gambling paradigm (Dreher et al, 2016). Hence, AR antagonism may have led to deficits in the recognition of social opportunity (Berghe, 2014;Fernald, 2017). Multiple sensory modalities are likely involved in an ND male's ability to recognize and act on social opportunity .…”
Section: Androgen Signaling Governs Multiple Aspects Of the Social Camentioning
confidence: 99%
“…Affiliative social motivation and behavior (sociability) are foundational for the development of close social bonds and the endurance of social groups across species. Despite this importance, there is pronounced variation in sociability in typical humans and in many vertebrate and invertebrate species . The extremes of this continuum in humans are observed in many neurodevelopmental disorders (NDDs) .…”
Section: Introductionmentioning
confidence: 99%
“…Despite this importance, there is pronounced variation in sociability in typical humans 1-4 and in many vertebrate and invertebrate species. [5][6][7][8][9][10][11][12] The extremes of this continuum in humans are observed in many neurodevelopmental disorders (NDDs). [13][14][15] Twin and family studies in humans, 2,16 and selection and population studies in animals, [17][18][19][20][21][22][23] show that individual differences in core dimensions of social behavior are heritable.…”
mentioning
confidence: 99%
“…Cichlid species exhibit many social behaviors that cannot be studied in traditional laboratory species—including complex social hierarchies; cooperative breeding; biparental and exclusively paternal care systems; maternal care and mouthbrooding; monogamous and lek-like mating systems; and male bower building (Emlen & Oring, 1977; Fernald, 2017; Kidd et al, 2012; Kidd et al, 2006). Recent studies have also demonstrated OT and AVP modulation of social behavior in cichlids, including species-specific parental and mating behaviors (Huffman et al, 2015; O’Connell et al, 2012; Oldfield & Hofmann, 2011).…”
Section: Cichlids and Lake Malawi Bower Buildersmentioning
confidence: 99%
“…Cichlids exhibit extraordinary social behavioral diversity, including many examples of repeated behavioral evolution, rapid behavioral divergence and behavioral plasticity within individuals (Emlen & Oring 1977;Balshine-Earn & Earn 1998;Klett & Meyer 2002;Maruska & Fernald 2010;Kidd et al 2012;). Cichlid species exhibit many social behaviors that cannot be studied in traditional laboratory species, including complex social hierarchies; cooperative breeding; biparental and exclusively paternal care systems; maternal care and mouthbrooding; monogamous and lek-like mating systems; and male bower building (Emlen & Oring 1977;Kidd et al 2006Kidd et al , 2012Fernald 2017). Recent studies have also demonstrated OT and AVP modulation of social behavior in cich-1...…”
Section: Comparative Investigations In Cichlidsmentioning
confidence: 99%